Photothermal actuation of levitated pyrolytic graphite revised - Steven Yee; Louisa Oney; Tyler Cosby; David P. Durkin; Hatem ElBidweihy (APL Materials, 2021)
The significant diamagnetism of pyrolytic graphite (PyG) allows it to be passively levitated above permanent magnet arrays and translated in the plane of these arrays via optical irradiation, which promotes applications in frictionless milli-scale robotics. Previous explanations for the translation effect have cited photothermal heating of levitated PyG and the thermal dependence of PyG’s magnetic susceptibility, as observed through measurements of samples at uniform temperatures. In this article, we offer a revision to the theory of photothermal actuation of levitated PyG. Through experiments and simulations, we demonstrate that the gradient of PyG’s diamagnetism with temperature—as measured for samples at uniform temperatures—is insufficient to explain the magnitude of forces required by the optically induced translation phenomenon. We hypothesize that the contrast in diamagnetism of PyG samples under asymmetric photothermal heating is at least an order of magnitude greater than that expected from measurements where the sample temperature is uniformly varied. We propose that the origin of the enhanced diamagnetic contrast under asymmetric optical irradiation is a photothermoelectric effect, which impacts the concentration of electrons in diamagnetically significant orbital states in graphite. To support this hypothesis, we take qualitative measurements, demonstrating the n-type thermoelectricity of PyG samples under optical irradiation while also characterizing the graphitic material with scanning electron microscopy/energy dispersive x-ray spectroscopy. We highlight the new understanding of the origin of the photothermal actuation through experiments using PyG samples with modified geometries that exhibit a pronounced preference in the axis of translation.